USE OF PROGESTERONE-BASED FTAI PROTOCOL FOLLOWED BY GnRH OR hCG TREATMENT ON DAY 6 POST-AI IN REPEAT BREEDER CATTLE - KUNDE, A A S; RAJU, M S; MURUGAVEL, K (The Indian Journal of Animal Reproduction, 2022)
Repeat breeder cattle (n=45) were synchronized using intravaginal progestational device (TRIU-B) based Co-Synch protocol. On day 6 post artificial insemination (AI), all the animals were administered (i.m.) either 10 μg GnRH analogue, (n=15), 1500 IU hCG (n=15) or normal saline (n=15). Pregnancy diagnosis was carried out on day 45 post-AI. Jugular vein blood was collected on day 6 and day 12 post-AI for serum progesterone estimations. On day 12 post-AI, serum progesterone values both overall as well as in the conceived animals were high (p<0.05) in hCG group compared to control. In GnRH, hCG and control group, the respective conception rate was 40%, 46.7% and 33.3%. In brief, administration of hCG on day 6 post AI improves subsequent luteal profile with tendency for better conception rate in repeat breeder cattle.